Transcriptional bursts and heterogeneity among cardiomyocytes in hypertrophic cardiomyopathy - Burkart, Valentin; Kowalski, Kathrin; Aldag-Niebling, David; Beck, Julia; Frick, Dirk Alexander; Holler, Tim; Radocaj, Ante; Piep, Birgit; Zeug, Andre; Hilfiker-Kleiner, Denise; dos Remedios, Cristobal G.; van der Velden, Jolanda; et al. (Frontiers in Cardiovascular Medicine, 2022)
Transcriptional bursting is a common expression mode for most genes where independent transcription of alleles leads to different ratios of allelic mRNA from cell to cell. Here we investigated burst-like transcription and its consequences in cardiac tissue from Hypertrophic Cardiomyopathy (HCM) patients with heterozygous mutations in the sarcomeric proteins cardiac myosin binding protein C (cMyBP-C, MYBPC3) and cardiac troponin I (cTnI, TNNI3). Using fluorescence in situ hybridization (RNA-FISH) we found that both, MYBPC3 and TNNI3 are transcribed burst-like. Along with that, we show unequal allelic ratios of TNNI3-mRNA among single cardiomyocytes and unequally distributed wildtype cMyBP-C protein across tissue sections from heterozygous HCM-patients. The mutations led to opposing functional alterations, namely increasing (cMyBP-Cc.927-2A>G) or decreasing (cTnIR145W) calcium sensitivity. Regardless, all patients revealed highly variable calcium-dependent force generation between individual cardiomyocytes, indicating contractile imbalance, which appears widespread in HCM-patients. Altogether, we provide strong evidence that burst-like transcription of sarcomeric genes can lead to an allelic mosaic among neighboring cardiomyocytes at mRNA and protein level. In HCM-patients, this presumably induces the observed contractile imbalance among individual cardiomyocytes and promotes HCM-development.